Digital Image Security Implementation With Uses Super Encryption Algorithm Myszkowski And The Algorithm Paillier Cryptosystem - EVAPIONA; Achmad Fauzi; Milli Alfhi Syari (Yayasan Kita Menulis, 2023)
This study aims to implement digital image security by applying two encryption algorithms, namely the Myszkowski algorithm and the Paillier Cryptosystem algorithm. Digital images are a very important form of data and are used frequently in a variety of applications, so protecting their security is a major concern. The encryption method proposed in this study uses a combination of the Myszkowski algorithm to randomize image pixels and the Paillier Cryptosystem algorithm to perform symmetric key encryption. At the experimental stage, qualitative and quantitative analysis was carried out on the performance of the encryption implemented on digital images. Testing is carried out by comparing the level of security and encryption speed of the two algorithms used. In addition, size analysis of encrypted images was also performed to evaluate the efficiency of the proposed system. The results of the study show that the use of a combination of the Myszkowski algorithm and the Paillier Cryptosystem algorithm provides a high level of security for digital images. In addition, the efficiency of this system has also been proven in producing efficient encryption image sizes, so that it can be implemented in image-based applications that require a higher level of security.